2019
DOI: 10.1111/myc.13013
|View full text |Cite
|
Sign up to set email alerts
|

Use of triazoles for the treatment of invasive aspergillosis: A three‐year cohort analysis

Abstract: Summary In a 3‐year cohort study of adult patients with proven or probable IA, fewer patients initially treated with isavuconazole experienced adverse events compared with voriconazole, but more patients required a change in therapy due to lack of clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Furthermore, due to its spectrum of activity against many non‐ Aspergillus moulds, isavuconazole is an attractive option in the setting of severe and prolonged immunosuppression where coinfection by more than one fungus may be of concern 179 . However, while real‐world data support the safety and tolerability profile of isavuconazole in haematological patients for the treatment of IFD, 180 reports of IFD breakthrough and failure are increasing in the setting of prophylaxis and treatment 181–184 …”
Section: Question 9: What Recommendations Should Guide the First‐line Antifungal Treatment Of Ia In Haematology/oncology Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to its spectrum of activity against many non‐ Aspergillus moulds, isavuconazole is an attractive option in the setting of severe and prolonged immunosuppression where coinfection by more than one fungus may be of concern 179 . However, while real‐world data support the safety and tolerability profile of isavuconazole in haematological patients for the treatment of IFD, 180 reports of IFD breakthrough and failure are increasing in the setting of prophylaxis and treatment 181–184 …”
Section: Question 9: What Recommendations Should Guide the First‐line Antifungal Treatment Of Ia In Haematology/oncology Patients?mentioning
confidence: 99%
“…179 However, while real-world data support the safety and tolerability profile of isavuconazole in haematological patients for the treatment of IFD, 180 reports of IFD breakthrough and failure are increasing in the setting of prophylaxis and treatment. [181][182][183][184] While both posaconazole oral suspension and delayedrelease tablets have demonstrated efficacy for prophylaxis of IA in haematology patients, and posaconazole is licensed for salvage treatment of invasive mould disease, there are limited published data to support its first-line use to treat IA. [185][186][187] However, a recently published multicentre, randomised controlled trial of posaconazole compared with voriconazole for first-line therapy of IA demonstrated non-inferiority of posaconazole to voriconazole for the outcomes of mortality and global clinical response, with improved tolerance to posaconazole compared to voriconazole.…”
Section: Azole-resistant a Fumigatus In Australiamentioning
confidence: 99%
“…145 High procalcitonin levels are associated with a risk of supratherapeutic levels after the loading dose, 342 and serum albumin levels affect VRZ levels. 110,171 Despite its efficacy, 343 frequent safety issues have been reported for VRZ. Cases reports and studies suggest that high levels are associated with toxicity.…”
Section: Vrz Trendsmentioning
confidence: 99%
“…Despite its efficacy, 343 frequent safety issues have been reported for VRZ. Cases reports and studies suggest that high levels are associated with toxicity.…”
Section: Tdm For Af Drugsmentioning
confidence: 99%
“…Twenty-seven consecutive adult patients had clinical sequencing in an evaluation of myeloid malignancy and were diagnosed with proven or probable IA from March 2015 through December 2017 (Figure 1A). 13…”
Section: Ia Cohortmentioning
confidence: 99%